Concepts and Measures of Saving: Selected Issues for South Africa. (4th May 2016) - Orthofer, Anna
Abstract: South African household savings rates have been declining steadily over the last five decades, raising concerns that the population structurally under‐saves. Against the background of new saving‐enhancing policy initiatives, this paper asks to what extent the concern is founded, and whether the measurement of saving is really appropriate to guide economic policy. Comparing different macroeconomic concepts and measurements of saving, we show that the measure of saving in the national accounts (the residual between income and expenditure) understates the household savings rate compared to other measures. Specifically, an alternative measure from the balance sheets (the change in wealth) yields a significantly higher and non‐declining figure. While households have not been "putting aside" their incomes, they have nevertheless grown richer, driven largely by the appreciation of asset valuations. We also examine the impact of taking non‐financial saving and wealth into account, and conclude that household sector saving on the aggregate is significantly higher than the national accounts suggest. However, these adjusted measures are most relevant for the upper tail of the income and wealth distribution, raising important distributional concerns.